Workers' Age and the Impact of Trade Shocks - Artuç, Erhan (World Bank, Washington, DC, 2012)
Do trade shocks affect workers differently because of their age? This paper examines the issue by estimating the lifetime mobility of workers based on the sectors in which they work. Using U.S. data, the paper shows that mobility costs rise with a worker's age and years of experience, but stay the same regardless of his or her education level. In addition, using a general-equilibrium simulation of counterfactual trade-liberalization policies in the metal manufacturing sector, the paper shows that trade shocks affect workers with higher mobility costs more, for both winners and losers of the policy shocks. But the effects taper off over a worker's lifetime, especially when they are close to retirement.